2005
DOI: 10.1002/hyp.5635
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing long-term records of dissolved CO2

Abstract: Abstract:The dissolved CO 2 concentration of stream waters is an important component of the terrestrial carbon cycle. This study reconstructs long-term records of dissolved CO 2 concentration for the outlets of two large catchments (818 and 586 km 2 ) in northern England. The study shows that:1. The flux of dissolved CO 2 from the catchments (as carbon per catchment area), when adjusted for that which would be carried by the river water at equilibrium with the atmosphere, is between 0 and 0Ð39 t km 2 year 1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…This suggests that a significant amount of DOC removal may happen close to its source. Hope et al (2001); Worrall and Burt (2005a) have shown that dissolved CO 2 release is a significant percentage of the carbon release from a catchment and is a component of the carbon cycle of peatlands that will always result in addition of CO 2 to the atmosphere. However, the amount of dissolved CO 2 released from a catchment is critically dependent upon in-stream processes (Jones and Mulholland, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a significant amount of DOC removal may happen close to its source. Hope et al (2001); Worrall and Burt (2005a) have shown that dissolved CO 2 release is a significant percentage of the carbon release from a catchment and is a component of the carbon cycle of peatlands that will always result in addition of CO 2 to the atmosphere. However, the amount of dissolved CO 2 released from a catchment is critically dependent upon in-stream processes (Jones and Mulholland, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Worrall et al . (2005) and Worrall and Burt (2005), based on carbon discharge data over three decades, determined that the amount of dissolved CO 2 produced in peat soils ranged between 9.6 and 25.6 t C km −2 year −1 and that this would decrease the predicted value of the net CO 2 sink by up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon flux depends on vegetation composition, organic matter input and substrate availability to enzymes (Davidson & Janssens 2006, Laiho 2006. Older peat formations can only decay, but decomposition and carbon release from newer peat layers may be offset by rates of new peat growth (Worrall & Burt 2005). Furthermore, fluvial export of carbon as undissolved particulate organic carbon (POC) is secondary to losses through gaseous exchange in eroding peatlands and at least equivalent to the net gaseous flux from intact peatlands (Worrall et al 2003, Evans et al 2006b).…”
Section: Soilsmentioning
confidence: 99%
“…A study of moorland fire frequency in the Pennines showed a high incidence during the hot dry summer of 1976 and dry spring of 2003, and the greatest frequency of fires tended to be on eroded bare peat . Water treatment plants downstream of blanket bogs can incur increased costs when DOC emissions rise following upland fires (Worrall & Burt 2005). A further complicating factor is that some moorland is regularly burnt as part of a deliberate management strategy to encourage new vegetation growth for game birds.…”
Section: Soilsmentioning
confidence: 99%
See 1 more Smart Citation